OPTIMASI FORMULA TABLET ATTAPULGITE DENGAN KOMBINASI LAKTOSA DAN AVICEL PH 101 TERHADAP MUTU FISIK TABLET MENGGUNAKAN SIMPLEX LATTICE DESIGN - Anisa Tri Utami; Vivin Nopiyanti; Widodo Priyanto (Jurnal Farmasi & Sains Indonesia, 2025)
Attapulgite is one of the drugs from the adsorbent class for anti-diarrhea. In the form of light cream-colored powder and very fine. This study aims to determine the effect of the combination of lactose and avicel PH 101 on the PHysical quality of attapulgite tablets and to obtain the optimum formula. Attapulgite tablets were made by wet granulation and formula optimization using the Simplex Lattice Design method using Design Expert software version 13 to find out the combination of lactose and avicel PH 101. Attapulgite tablets were made into 8 formulas with variations in comparing the proportions of lactose and avicel PH 101 according to the results range of simplex lattice designs. Critical point parameters and optimum formulas were obtained from the response of hardness, brittleness, and disintegration time, and were verified using the one-sample t-test statistical program. The results of this research were variations in concentration of all attapulgite tablet formulas resulting in good PHysical quality of the tablets. The combination of lactose and avicel PH 101 has the effect of increasing hardness, reducing brittleness, and speeding up disintegration time. The proportion of lactose 66,739 mg and avicel PH 101 33,261 mg produces the optimum formula for attapulgite tablets with the best PHysical quality of the tablets.